Proceedings of the 11th International Conference on Simulation and Modeling Methodologies, Technologies and Applications 2021
DOI: 10.5220/0010540100002995
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Robot Design for Cleaning Solar Panels

Abstract: The accumulation of dust particles on the solar panels decrease the total amount of solar energy received by the Photovoltaic panel (PV) and, it has also been proven that the increase of temperature reduces the overall efficiency. These effects have been studied by different researchers based on collected data comparison. As both of these parameters have a negative effect on the efficiency of the solar panel, it is essential to keep them clean and at low temperatures. The use of technologies, such as robots, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results found that the exposure of 12 months under different seasons reduced the PV system's efficiency by 24.5, 15.6, 5.14, and 1.95% in summer, winter, postmonsoon, and monsoon, respectively. Also, [25] mentioned that the long periods without rain, such as the summer, dust accumulation can lead to daily losses and can be as high as 20%. Moreover, [26] concluded that soiling losses of PV panels due to dust lead to a significant decrease in the yield of solar energy and result in economic losses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results found that the exposure of 12 months under different seasons reduced the PV system's efficiency by 24.5, 15.6, 5.14, and 1.95% in summer, winter, postmonsoon, and monsoon, respectively. Also, [25] mentioned that the long periods without rain, such as the summer, dust accumulation can lead to daily losses and can be as high as 20%. Moreover, [26] concluded that soiling losses of PV panels due to dust lead to a significant decrease in the yield of solar energy and result in economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages of the robotic device outlined in the previous paragraph, some suggestions have been made for multiple automated systems to solve the problem of dust accumulation on the surfaces of solar panels through robots. Hence, [25] innovated a robot design capable of cleaning and cooling the PV panels, based on images acquired to create a maintaining periodic cleaning system to increase PV efficiency. In the final analysis, the preliminary finds demonstrated the possibility of this approach for the accomplishment of this task.…”
Section: Introductionmentioning
confidence: 99%